Correlation between percutaneous patent foramen ovale closure and recurrence of unexplained syncope - Wang, Xianwen; Liu, Xiangwei; Zheng, Lulu; Liu, Yubo; Guan, Zhengyan; Dai, Jingyi; Chen, Xiaobin (Frontiers in Neurology, 2023)
Background The relationship between patent foramen ovale (PFO) and unexplained syncope remains to be illustrated. Therefore, this study aimed to explore the outcomes and prognostic factors for syncope recurrence after PFO closure. Methods Patients with both large right-to-left shunting (RLS) PFO and unexplained syncope who visited the cardiovascular department of Xiangya Hospital Central South University from 1 January 2017 to 31 December 2021 were consecutively enrolled in our study. The recurrence rate of syncope was compared between the non-closure group (n = 20) and the closure group (n = 91). Results A total of 111 patients were finally included. After 31.11 ± 14.30 months of follow-up, only 11% of patients in the closure group had recurrent syncope, which was much lower than that of the non-closure group (11.0 vs. 35%, P = 0.018). We further investigated the possible prognostic factors for syncope recurrence in the closure group and found syncope occurring more than five times preoperatively, hypertension, and residual RLS at 12-month follow-up were significantly correlated with a higher number of recurrences. Conclusions PFO closure reduced the recurrence rate of unexplained syncope. The efficacy of prevention was prognosticated by factors including the presence or absence of syncope induction, the frequency of syncope episodes, and the presence or absence of hypertension. Syncope recurrence was also related to residual shunts post closure.